2020
DOI: 10.2147/cmar.s268075
|View full text |Cite
|
Sign up to set email alerts
|

<p>Clinical Characteristics and Prognostic Analysis of Gynecologic Cancer with Spinal Metastases: A Single-Center Retrospective Study</p>

Abstract: Objective The purpose of this study is to provide key information on the clinical characteristics, surgical treatment, and potential prognostic factors in patients with metastatic spinal gynecologic cancer (MSGC), with a view to their application in clinical practice. Methods From January 2010 to January 2020, we performed a retrospective analysis of 14 patients with MSGC who underwent surgical treatment in a single center. Surgical treatment was performed on 14 patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 29 publications
1
2
0
Order By: Relevance
“…The longest median overall survival time found in this review was 45 months; however, most studies indicate a median overall survival of ~12 months. In agreement with the literature, our review revealed that GC bone metastases most affected the axial skeleton and in particular the vertebral column [ 13 ]. The causes of this trend are not yet fully understood, but it has been hypothesized that the cellular and molecular characteristics of cancer cells and the tissues to which they metastasize are critical and affect the pattern of metastatic spread; however contradictory or inconclusive results have been reported [ 14 , 55 ].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The longest median overall survival time found in this review was 45 months; however, most studies indicate a median overall survival of ~12 months. In agreement with the literature, our review revealed that GC bone metastases most affected the axial skeleton and in particular the vertebral column [ 13 ]. The causes of this trend are not yet fully understood, but it has been hypothesized that the cellular and molecular characteristics of cancer cells and the tissues to which they metastasize are critical and affect the pattern of metastatic spread; however contradictory or inconclusive results have been reported [ 14 , 55 ].…”
Section: Discussionsupporting
confidence: 90%
“…Bone metastases from GCs were detected in about 1.1–5.2% of patients with CC [ 8 ], in ~1.2% of patients with OC [ 9 ], in 2–8% of patients with EC [ 10 ], and rarely in vulvar (VuC) [ 11 ] and vaginal cancers (VaC) [ 12 ]. Despite the uncommon incidence of GC bone metastases, the prolonged local disease control and the easy availability of advanced imaging techniques are increasing this incidence, and more and more anecdotal evidence is reported in the literature [ 8 , 13 , 14 ]. Not unexpectedly, these complications seriously affect quality of life, performance status, independent functioning, and survival.…”
Section: Introductionmentioning
confidence: 99%
“…Gynecologic cancers may occur to women of all ages worldwide; the diseases often result in disruptions in physical and mental health, quality of life, and even early death [ 21 , 22 ]. Some patients develop metastases after treatment even though with the strategies of standardized treatments of tumors in recent years [ 23 ].…”
Section: Introductionmentioning
confidence: 99%